Zinc Oxide Nanoparticles-Enriched Extender Enhances Cryosurvival and Antioxidant Defense of Buffalo Spermatozoa - Patel, Richakumari M; Parmar, Kirankumar H; Chaudhari, Meet T; Chaudhari, Dinesh V; Pathan, Mohsin M; Parmar, Jignesh J (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study was conducted at the Central Sperm Station of the College of Veterinary Science in Anand, to evaluate the effect  of zinc oxide nanoparticles (ZnONPs) on the post-thaw quality of buffalo bull semen. A total 18 ejaculates from four mature healthy  breeding bulls were collected using an artificial vagina and evaluated for semen quality. Semen samples showing >70% initial motility  were diluted in Tris fructose egg yolk glycerol (TFYG) extender, divided into four aliquots supplemented with 0 (control), 10, 25, and 50  µg/mL ZnONPs, equilibrated at 4°C, frozen in liquid nitrogen vapour, and stored at -196 °C overnight. Post-thaw semen was evaluated  for sperm motility, viability, morphology, acrosome integrity, plasma membrane integrity (HOST), lipid peroxidation (MDA), and total  antioxidant capacity (TAC). Statistical analysis revealed that a significant (p
Keywords: Antioxidant status, Buffalo bulls, Zinc oxide nanoparticles, Cryopreservation, TFYG extender